LOCAL SOCIAL ROLE IN FOREST PREVENTION AND FOREST PLANNING BY OPEN COUNTRIES - Hutabarat, Dany Try Hutama; Fauzan, Aan; Piranda, Dea Resti; Sinaga, Dessy Zulfianti; Putri, Erga Eka; Sinambela, Ibrahim; Hakim, M. Fauzan; Lubis, Rafly Aulia; Iswandi, Rizky; Dalimunthe, Septian Rizky; Satria Alvin Sitorus, Akmal (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
The majority of Indonesians make their living from farming, which requires a lot of area to grow crops. To produce fresh land for farmers, a small amount of forest must be cleared. The cost of land cannot be increased by cutting down and burning trees and forests, according to the legislation. However, there are several exceptions to local rules, such as burning up to 2 hectares of land per family head, growing local kinds, and encircling themselves with fire traps to prevent disease transmission, but not to the environment. The study's goal was to examine into the involvement of local sages in land clearance, forest burning, and land burning, as well as the establishment of land clearing operations against police officers who broke local laws. This research method combines a legal (sculpture) and a conceptual approach. The findings demonstrate the importance of local wisdom in large-scale forest fire prevention through constitutional acknowledgment of local wisdom.